A novel parameter to evaluate fatigue crack closure: Crack opening ratio. (December 2020) - Duan, Q.Y.; Li, J.Q.; Li, Y.Y.; Yin, Y.J.; Xie, H.M.; He, W.
Highlights: A new parameter called C O R is proposed to evaluate the fatigue crack closure. C O R is constant regardless of the measurement positions behind crack tip. C O L can be evaluated in the whole process of fatigue tests by C O R ¯ - C method. Abstract: A new parameter called crack opening ratio ( C O R ) is proposed to evaluate the fatigue crack closure. C O R is expressed as a percentage that can be devoted to identifying the degree of crack opening and to determining the value of crack opening load ( C O L ). Interestingly, theoretical analysis indicates that C O R is invariant in different measurement positions behind the crack tip. To verify the effectiveness and reliability of C O R -based methods, fatigue tests of superalloy G H 4169 in complex environment, overload and high temperature ( 650 °C), are conducted with compact tension ( C T ) specimens. By means of bi-prism-based single-lens 3D digital image correlation ( BSL 3 D DIC ) technique, the full-field fatigue deformation near the crack tip is in situ measured, based on which the C O L is characterized throughout the whole process of fatigue tests. Compared to some other classical methods, including stress intensity factor-crack opening load method ( S I F - C O L ), crack opening displacement-compliance method ( C O D - C ), and crack-profiles method ( C - P ), the C O R -based methods have shown a consistent result and better anti-noise capability. Concretely, C O R -based methods are not sensitive to the measurement positions, thus the results have little dispersion and can be derived from full-field data. As a result, the determined value of C O L is relevant to the characteristics of the region (not just the discrete points), which is steady and reliable.